Pengaruh DPS, EPS, dan ROA Terhadap Harga Saham - Ifadhila (Fakultas Hukum dan Ekonomi Bisnis, 2023)
The capital market is a meeting place for people with more funds to invest and people who need funds such as companies to improve their companies. The large number of losses that occur in the world of capital markets makes this research important. The results of this study provide information that earnings per share (eps) and dividend per share (DPS) in a company have an important role in providing information to investors. Good earnings per share and dividend per share show that the company has good financial performance. This is supported by the results of the multiple linear regression analysis methods which state that earnings per share (eps) and dividend per share (DPS) have a positive and significant effect on stock prices. But ROA is not significant to stock prices.EPS